2014
DOI: 10.1177/0957650914547605
|View full text |Cite
|
Sign up to set email alerts
|

Research on operating characteristics of single slide valve capacity control mechanism of the single screw refrigeration compressor

Abstract: In the single screw refrigeration compressor (SSRC), the single slide valve capacity control mechanism (SVCCM) is the functional component used to achieve capacity control under different load conditions with cooperation of screw rotor and housing. In this paper, a new calculation model considering internal compression and leakage is presented to research the capacity control process and built-in volume ratio control process. By this model, the actual capacity and built-in volume ratio at different slide valve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…In order to obtain the effective discharge and bypass area, the equation of profile VL, VR, and the boundary curves surrounding the bypass port should be set up. The equation of VL can be obtained according to the literature [19]:…”
Section: Geometric Model Of the Csvmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to obtain the effective discharge and bypass area, the equation of profile VL, VR, and the boundary curves surrounding the bypass port should be set up. The equation of VL can be obtained according to the literature [19]:…”
Section: Geometric Model Of the Csvmentioning
confidence: 99%
“…Following this, Zhou et al investigated the capacity adjustment mechanisms of the slide valve and the performance of compressors utilizing this single-control slide valve device [18]. Wang et al [19] presented a mathematical calculation method to study the capacity control mechanism of single-slide valve. Variable frequency technology can regulate compressor capacity by altering the compressor's rotational speed.…”
Section: Introductionmentioning
confidence: 99%
“…It suggested that the slide valve installation angles should be as large as the installation space permits, and the fixed type slide should stop with a length of 20-25% of the rotor length when the external pressure ratio was single or else the moveable type. Wang et al [106] adopted a similar method to investigate the effects of slide valve structure parameters on the operation process of a refrigeration SSC under part-load conditions and compared the capacity control process with the built-in volume ratio control process. Further, they [107] studied the thermal dynamic characteristics of a refrigeration SSC with the single slide valve capacity control and the frequency conversion control under part-load conditions.…”
Section: Control Of Capacity and Built-in Volume Ratiomentioning
confidence: 99%
“…However, it is difficult to apply these results directly to other occasions due to the lack of mechanism analysis. Through geometric research, Wang et al 94 found that the adjustment range of displacement increased when the initial position of the bypass orifice is closer to the exhaust side. Moreover, the ratio of internal volume increases as the initial position of valid exhaust port approaches the exhaust side.…”
Section: Study On Working Process Of Sscmentioning
confidence: 99%